"Local and Contemporary": Reception, Community and the Poetry of Ann Julia Hatton ("Ann of Swansea"). Issue 4 (2nd October 2017) - Edwards, Elizabeth
ABSTRACT: This article reads the poetry of "Ann of Swansea", Ann Julia Hatton (née Kemble, 1764–1838), in the context of recent scholarship that emphasizes the expansive but networked and responsive nature of Romantic-period women's writing. Building on recent research, it shows Hatton as part of a writerly community shaped by poets and novelists into what Harriet Guest has termed "a shared cultural identity forged through sociable and literary exchanges". It goes on to consider Hatton as a Welsh writer by choice rather than background or birth, claiming a place within Wales's bardic tradition through her identification with Swansea and the surrounding south coast. This article concludes with a close reading of the reception history of Hatton that offers the category of the local as a new direction within histories of women's writing and notions of literary recovery. In this way, it suggests ways of reconfiguring Romantic-period literary culture to account more fully for the work and reception of non-metropolitan writers.